SPE Annual Technical Conference and Exhibition 2019
DOI: 10.2118/195808-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study of Degradable Fibers With and Without Guar Gum As A Proppant Transport Agent Using A Large Scale Slot Equipment

Abstract: Hydraulic fracturing with slickwater is a common practice in developing unconventional resources in North America. The proppant placement in the fractures largely determines the productivity of the well as it affects the conductivity of fractures. Despite the wide use of the slickwater fracturing and the importance of the proppant placement, the proppant transport is still not fully understood and the efficiency of the proppant placement is mostly bound to the changes to proppant properties, friction reducers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the contrary, larger-sized proppants form sand beds with good characteristics at the end close to the inlet; however, they do not favour proppant particles being transported to deeper fractures. [26][27][28] Another group of researchers studied proppant transport in different types of fracture (e.g., single, complex, inclined, and contracting fracture). [29][30][31][32][33][34][35] Some of these researchers, after studying the influence of fractures with a contracting width on proppant transport, concluded that irregular changes in fracture width will lead to changes in the flow pattern of sand-carrying fluid to generate a vortex, resulting in continuous damage to the fluidized layer by eddy particles, so that more stationary particles are resuspended, transported to deeper fractures, and the height of the sand bed is thus reduced.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, larger-sized proppants form sand beds with good characteristics at the end close to the inlet; however, they do not favour proppant particles being transported to deeper fractures. [26][27][28] Another group of researchers studied proppant transport in different types of fracture (e.g., single, complex, inclined, and contracting fracture). [29][30][31][32][33][34][35] Some of these researchers, after studying the influence of fractures with a contracting width on proppant transport, concluded that irregular changes in fracture width will lead to changes in the flow pattern of sand-carrying fluid to generate a vortex, resulting in continuous damage to the fluidized layer by eddy particles, so that more stationary particles are resuspended, transported to deeper fractures, and the height of the sand bed is thus reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The fracturing fluid transports the proppant during hydraulic fracturing to obtain the artificial fracture diversion channel . The high-quality hydraulic fracturing fluid aims to create sufficient fractures for oil and gas flow and control the proppant transportation . In practice, the water-based fracturing fluid is the most cost-effective choice.…”
Section: Introductionmentioning
confidence: 99%